Rheumatic fever: incidence in Pinar del Rio from 1986 to 1996 - Raimundo López Rodríguez; José A. González Rodríguez; Orlando Martínez Hernández; Fidel Manuel Cáceres Lóriga; Porfirio Nordet Cardona; Alberto Hernández Cañero (ECIMED, 2014)
The incidence of acute rheumatic fever from 1986 was studied among the habitual residents of the province of Pinar del Rio aged 5-25. All those patients who probably suffered from the disease (codes 390-398, 421-428, 710 and 710-715) and were hospitalized during that period were registered. The criteria of Jones were modified and applied to verity the diagnosis. The incidence rates decreases as time went by: in 1986 it was 18.6 x 100 000 inhabitants (12.2 for a first attack and 6.4 for recurrences) and in 1996 it was 2.5 x 100 000 inhabitants (2.1 for a first attack and 0.4 for recurrence). A reduction was also observed smong those with sequelas on discharge due to the fact that the magnitude of the disease. diminished.